A concept design stage of modular buoy / Muhammad Umarul Asyraf Ibrahim and Rohaizad Hafidz Rozali - Ibrahim, Muhammad Umarul Asyraf; Rozali, Rohaizad Hafidz (2019)
The objective of this project is to present the concept design stage of a buoy. The buoy is the structure which is floating on the sea surface has been used for several applications measuring oceanographic, meteorically, chemical and biological parameters. The buoy is also used to show the direction of the sea route to ship during sailing. Generally, the conventional material of buoy is steel. Steel buoy has many advantages such as high strength and easy manufacturing using cutting and welding process to take shape. However, it can lead to marine pollution due to steel corrosion and maintenance cost due to its heavy weight. To overcome this problem, Wave scan buoy using polyethylene which is light and environmentally friendly are developed. The design and application of Wave scan buoy for a deep water tsunami detection system for Malaysia are discussed. The Wave scan superstructure shape was chosen for reference. In this study, the researchers will design the buoy from existing design body to the modular type concept design. The concept design includes the principal dimensions and identifies all major design trade-offs. Concept design process example was carried out using Computer Aided Design (CAD) software to speed up the design process. The concept design determines whether the modular buoy can be a feasible design to continue development in the preliminary design stage. The intent of the concept design is to provide the designer to resolve all design trade-offs. The sooner you resolve the major design trade-offs, the less work you will have to do to complete the design and the more successful it will be.